2021
DOI: 10.1210/clinem/dgab403
|View full text |Cite
|
Sign up to set email alerts
|

Insulin Secretion Predicts the Response to Antidiabetic Therapy in Patients With New-onset Diabetes

Abstract: Aim To identify predictors for individualization of antidiabetic therapy in patients with new onset T2DM. Research Design and Methods 261 drug naïve participants in the EDICT study, with new onset diabetes, were randomized in a single-center study to receive: (1) metformin followed by glipizide and then insulin glargine upon failure to achieve HbA1c <6.5%, or (2) initial triple therapy with metformin/pioglitazone/ exen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 29 publications
0
4
0
Order By: Relevance
“…It should be noted that the enhanced performance of pioglitazone plus a GLP‐1RA over conventional therapy in EDICT and insulin therapy in the Qatar study in Group 1 was attenuated in participants in Group 3. We previously demonstrated that higher residual beta‐cell function in T2DM patients predicts a better response to glucose‐lowering therapies independent of disease duration and HbA1c level 21‐23 . This observation emphasizes the importance of residual beta‐cell function in achieving the goal of glycaemic control.…”
Section: Discussionmentioning
confidence: 87%
See 1 more Smart Citation
“…It should be noted that the enhanced performance of pioglitazone plus a GLP‐1RA over conventional therapy in EDICT and insulin therapy in the Qatar study in Group 1 was attenuated in participants in Group 3. We previously demonstrated that higher residual beta‐cell function in T2DM patients predicts a better response to glucose‐lowering therapies independent of disease duration and HbA1c level 21‐23 . This observation emphasizes the importance of residual beta‐cell function in achieving the goal of glycaemic control.…”
Section: Discussionmentioning
confidence: 87%
“…We previously demonstrated that higher residual beta-cell function in T2DM patients predicts a better response to glucoselowering therapies independent of disease duration and HbA1c level. [21][22][23] This observation emphasizes the importance of residual beta-cell function in achieving the goal of glycaemic control.…”
Section: Discussionmentioning
confidence: 99%
“…Over 72 months, the latter intervention was effective even with initial HbA1c > 9%, appearing to be mediated by sustained improvement in beta cell function as well as in insulin sensitivity 1 . In the study, approximately one quarter of those randomized to metformin alone had sustained stable glycemic control with metformin, with Abdul‐Ghani showing evidence that these were the patients with higher baseline levels of beta‐cell function, as measured using the ratio of C‐peptide levels before to that 120 min after glucose loading, whereas baseline HbA1c was not predictive of response to metforminmonotherapy 1,2 . The similarly structured Qatar study enrolled patients with more longstanding T2D on metformin and sulfonylurea randomized to the addition of pioglitazone plus a glucagon‐like peptide‐1 receptor agonist (GLP‐1RA) vs addition of insulin, similarly showing sustained improvement with the former approach 3 .…”
Section: The Beta Cell In Diabetesmentioning
confidence: 96%
“… 1 In the study, approximately one quarter of those randomized to metformin alone had sustained stable glycemic control with metformin, with Abdul‐Ghani showing evidence that these were the patients with higher baseline levels of beta‐cell function, as measured using the ratio of C‐peptide levels before to that 120 min after glucose loading, whereas baseline HbA1c was not predictive of response to metforminmonotherapy. 1 , 2 The similarly structured Qatar study enrolled patients with more longstanding T2D on metformin and sulfonylurea randomized to the addition of pioglitazone plus a glucagon‐like peptide‐1 receptor agonist (GLP‐1RA) vs addition of insulin, similarly showing sustained improvement with the former approach. 3 Abdul‐Ghani reviewed the evidence of improvement in beta cell function of the GLP‐1RA liraglutide, 4 but also showed improved insulin secretion with pioglitazone, 5 over time well‐exceeding the effect of sulfonylurea.…”
Section: The Beta Cell In Diabetesmentioning
confidence: 99%